2013
DOI: 10.1007/s10493-013-9723-5
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to Rhipicephalus microplus infestations in pre-sensitised cattle with differing phenotypes of infestation

Abstract: The blue tick, Rhipicephalus microplus, threatens cattle production in most tropical and subtropical areas of the world. Delayed skin hypersensitivity reactions are thought to cause Nguni cattle to be more resistant to R. microplus than Bonsmara cattle yet the cellular mechanisms responsible for these differences have not been classified. Tick counts and inflammatory cell infiltrates in skin biopsies from feeding sites of adult R. microplus ticks were determined in 9-month-old Nguni and Bonsmara heifers to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Different types of immune reactions can also be included in the general scope of tick toxicoses [3,27]. Immediate and delayed skin hypersensitivity was reported in cattle exposed to R. microplus and R. decoloratus antigens [28,29], and in dogs exposed to A. cajennense antigens [30]. …”
Section: Resultsmentioning
confidence: 99%
“…Different types of immune reactions can also be included in the general scope of tick toxicoses [3,27]. Immediate and delayed skin hypersensitivity was reported in cattle exposed to R. microplus and R. decoloratus antigens [28,29], and in dogs exposed to A. cajennense antigens [30]. …”
Section: Resultsmentioning
confidence: 99%
“…Although the ecotypes tend to have specific phenotypes with regard to colour and body and or head conformation, genetic differentiation has not been confirmed. Studies to date has confirmed adaptability traits (Marufu et al 2011(Marufu et al , 2014 of the Nguni and identified genomic regions underlying tick resistance (Mapholi et al 2015). In this study the focus was on the genetic diversity and population structure of the known and unknown ecotypes based on microsatellite markers.…”
Section: Discussionmentioning
confidence: 97%
“…[4] reported that Mashona cattle were more resistant to ticks and had high calving and weaning rate under marginal environmental conditions characterising most smallholder areas when compared to some exotic breeds. The resistance to ticks in sanga breed has been attributed to coat characteristics such as colour, hair length and density [48], grooming behaviour and delayed cutaneous hypersensitivity reaction to tick infestation [65]. An understanding of the mechanisms behind genetic resistance to ticks and TBD in livestock species could improve breeding programmes to develop animals that are more resistant and productive [62].…”
Section: Characterisation and The Adaptive Traits Of Indigenous Beef mentioning
confidence: 99%